(untitled) (Advancements in Homeopathic Research, 2025)
condition with multifactorial etiology, including hormonal imbalance, nutritional deficiencies, stress, and environmental triggers. Despite the availability of conventional therapies, their limitations have led to increasing interest in alternative and homeopathic solutions. This study aimed to evaluate the real world effectiveness and physician satisfaction associated with Zauber™ Hair Drops, a homeopathic formulation, in the management of hair fall and alopecia.Materials & Methods: A post-marketing survey was conducted using a structured Google Form circulated among various healthcare channels including practitioners, dealers and end consumers across India for diversified responses. The survey collected data on indications treated, onset of clinical improvement, perceived effectiveness, patient outcomes, and any reported adverse events. Descriptive analysis was performed on the physician responses. Results: A total of 38 responses were received from the survey out of which majority of participation was from clinical practitioners. Of the 24 participating physicians, 87.5% prescribed Zauber™ for hair fall, with the remainder using it for scalp concerns like dandruff or irritation. Approximately 79.2% rated its effectiveness between 4 and 5 on a 5-point scale, while 80% observed clinical improvement within two weeks of use. Notably, 91.7% of doctors expressed willingness to recommend the product. No adverse effects were reported. These findings are supported by preclinical studies demonstrating anti-androgenic activity and hair follicle stimulation in a testosterone induced alopecia model. Conclusion: Zauber™ Hair Drops had high physician satisfaction and positive therapeutic effects for treating chronic hair loss and scalp diseases. Its properties like targeted and rapid action, good tolerability, and natural multi-targeted strategy makes it a viable alternative to conventional therapies.